Impairment of quality of life in patients with antiphospholipid syndrome. (October 2015) - Zuily, S; Rat, A-C; Regnault, V; Kaminsky, P; Mismetti, P; Ninet, J; Baillet, N; Magy-Bertrand, N; Pasquali, J-L; Lambert, M; Pasquier, E; Lorcerie, B; et al.
Objectives: Health-related quality of life (HRQoL) has not been fully explored in antiphospholipid syndrome (APS); therefore, we compared HRQoL between APS patients and the general population and assessed the impact of thromboembolic history. Methods: HRQoL was measured in a multicentre cohort study by the Medical Outcomes Study Short-Form 36 (MOS-SF-36) questionnaire. HRQoL scores were compared to the French general population norms. Factors significantly associated with an impaired HRQoL were identified. Results: A total of 115 patients with aPL and/or systemic lupus erythematosus (SLE) were included (mean age 42.7 ± 14.1 years old, 86 women). In 53 patients APS was diagnosed. Compared to general population norms, patients with APS had an impaired HRQoL. SLE-associated APS patients had the worst HRQoL scores (physical component summary (PCS)=40.8 ± 10.6; mental component summary (MCS)=40.6 ± 16.5) in comparison with SLE or aPL patients without thromboembolic history. In APS patients, history of arterial thrombosis significantly impaired HRQoL (PCS score: 42.2 ± 9.4 vs 49.2 ± 8.5; MCS score: 33.9 ± 13.7 vs 44.6 ± 10.3). Conclusion: Compared to the general population, APS patients experienced a lower HRQoL. In these patients, a history of arterial thrombosis significantly impaired HRQoL. Therefore, measurements of HRQoL should be included in APS patient management to assess the burden of the disease from a patient's perspective and to provide patients with the support they need.